Colchicine (a high-priced alkaloid) accumulation and HPTLC quantification in different stages of in vitro developed tuber of Gloriosa superba L. - Dipika Rathod; Jitendriya Panigrahi; Illa Patel (SpringerOpen, 2021)
Abstract Background Gloriosa superba L. belongs to Colchicaceae, which is an important medicinal plant containing high-priced alkaloid colchicines and other potent phytochemicals. Due to its extensive importance at the industrial level, this plant is overexploited. Moreover, indiscriminate harvesting for raw material leads to a decline in the population of this plant in the natural environment. Thus, the present study deals with the optimization of colchicine accumulation from the different intervals of in vitro and in vivo tubers of Gloriosa. Result To obtain in vitro tuberization, shoot tip explants were inoculated on Murashige and Skoog medium prepared with 3 mg/l BA and 0.5 mg/l Kn + 1 mg/l 2, 4-D followed by 2 mg/l BA + 0.2 mg/l NAA. In the high-performance thin-layer chromatography study (HPTLC), the linearity range of colchicine was set at a concentration range of 100-1000 ng/spot with a regression value (r) of 0.99. Its R f value (0.25) was recorded at 254 nm. The colchicine amount in the in vivo tuber was 7.75 ± 0.25% dry weight, while the nearby amount of 7.7 ± 0.40% dry weight of colchicine was produced from 2 weeks in vitro old tuber. This value was followed by the 4th-week old tuber with 6.35 ± 0.17% dry weight and then a gradual decrease in its accumulation. Conclusion The significant results for the accumulation of colchicine at different stages were observed. Hence, this strategy of colchicine production creates a new possibility for improved production of colchicine under in vitro conditions which will be helpful to various pharmaceutical industries without damaging the plants from the natural environment. Graphical abstract